Declining Condom Use Among Sex Workers in Western Australia - Selvey, Linda A.; Hallett, Jonathan; McCausland, Kahlia; Bates, Julie; Donovan, Basil; Lobo, Roanna (Frontiers in Public Health, 2018)
Since the emergence of the HIV pandemic in the 1980s, high rates of condom use for penetrative sex have been reported among sex workers in Australia. The sex industry in Australia and elsewhere has changed over the previous decade with increasing proportions of sex workers working privately and lower proportions of sex workers working in brothels. There has also been some evidence of reductions in condom use, particularly during penetrative oral sex. We therefore decided to investigate sex workers’ use of condoms during penetrative sex with clients. Methods This was a cross-sectional mixed methods study of sex workers in Western Australia. The study involved an environmental scan of the sex industry in Western Australia, visits to brothels and other sexual services premises, a survey of sex workers and in-depth interviews. Results We surveyed 354 male, female and transgender sex workers in Western Australia. We found unexpectedly low rates of reported condom use with clients for all forms of penetrative sex. Of respondents who reported providing this type of service, 33% reported that all clients usedcondom use with clients condoms always during oral sex, 69% during vaginal sex and 59% during anal sex. High levels of client demand for condomless sex was also reported, with 42% of sex workers reporting that all or most clients requested condomless oral sex. Increasing client demand, fear of losing clients and the ability to charge more for condomless sex were reported reasons for providing this service. Conclusions There has been an apparent increase in sex workers reporting condomless penetrative sex with clients in Western Australia compared to a previous cross-sectional study. An increase in private sex work and client demand for condomless sex together with an economic downturn leading to increased competition for clients may be important contributing factors.